Green synthesis of silver nanoparticles using carbon quantum dots - Lê, Thị Hòa; Nguyễn, Thị Kim Chinh; Nguyễn, Thị Thu Hương; Trần, Thái Hoà (Hue University Journal of Science: Natural Science, 2025)
Carbon quantum dots (CQDs), synthesized from betle leaves collected in Hue City, were used as both a reducing agent and a protective agent to synthesize silver nanoparticles (AgNPs). This is a "green synthesis" method, which is environmentally friendly, simple and highly effective. The factors affecting the formation of composite materials were investigated. The CQDs material has a size of about 5 nm, and the silver material on the CQDs (AgNPs/CQDs) has a UV-Vis absorption peak in the wavelength range of 400–440 nm, a size of about 30 nm and is stable for about 15 days of storage.